Evaluation of Pupillary Diameter in Preschool Children - Lavezzo, Marcelo Mendes; Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP]; Hirai, Flavio E. (Taylor & Francis Inc, 2009)
Few quantitative data exist on pupil diameter, particularly in children. In this article we describe an analysis of pupil diameter and pupil area in normal preschool children during attentive gaze (AG) and spontaneous gaze (SG) using digital imaging. The pupil diameter and pupil area of 200 preschool children aged 4 to 6 years were evaluated. The images were recorded with a digital camera, transferred to a computer, processed by movie software and submitted to the Invert filter of Adobe Photoshop (R) software. Three consecutive measures of pupil diameter and pupil area were taken for both eyes during AG and SG. Arithmetic means of each parameter were calculated and data were expressed in millimeters. Mean pupil diameter was similar for both eyes, presenting values of 4.9 mm during AG and 4.1 mm during SG. Mean pupil area was also similar for both eyes, presenting values of 15.6 mm(2) and 9.1 mm(2) during AG and SG, respectively. There were no differences between boys and girls. However, 6-year-old children showed lower pupil diameter and area under both evaluation conditions.
Keywords: Pupil diameter; pupil area; attention; preschool children; digital imaging